Relationship between peripapillary vessel density and visual field in glaucoma: a broken-stick model. Issue 7 (11th August 2020) - Song, Min Kyung; Shin, Joong Won; Jo, Younhye; Won, Hun Jae; Kook, Michael S
Abstract : Background/Aims: To determine the tipping point at which peripapillary vessel density (pVD), measured using optical coherence tomography angiography (OCT-A), is associated with detectable visual field (VF) loss in cases of open-angle glaucoma (OAG). Methods: Peripapillary retinal nerve fibre layer (pRNFL) thickness and pVD were measured using OCT and OCT-A in 166 healthy participants, those with suspected glaucoma and patients with early-stage OAG. All participants were Koreans. A broken-stick model was used to determine the tipping points below which pRNFL thickness (pRNFLT) or pVD reduction was associated with significant VF loss. The slopes were computed above and below the tipping points for the relationship between pVD, pRNFLT and VF sensitivity (VFS). Results: Tipping points were detected for pRNFLT globally and in the inferior and superior quadrants, at which there were significant differences between the slopes above and below the tipping points. The slopes above the tipping points were approximately zero. However, no tipping point was found for pVD in the global area or regional sectors. Conclusion: The relationship between pVD and VFS does not show a tipping point. This suggests that the correlation between pVD-VFS may be linear and stronger than that of pRNFLT-VFS, even at the early stage of glaucoma.